Introduction to Simulink with engineering applications - Karris, Steven T. (Orchard Publications, 2006)
Annotation This text is an introduction to Simulink, a companion application to MATLAB. It is written for students at the undergraduate and graduate programs, as well as for the working professional. Although some previous knowledge of MATLAB would be helpful, it is not absolutely necessary; Appendix A of this text is an Introduction to MATLAB to enable the reader to begin learning both MATLAB and Simulink to perform graphical computations and programming. Chapters 2 through 18 describe the blocks of all Simulink libraries. Their application is illustrated with practical examples through Simulink models, some of which are supplemented with MATLAB functions, commands, and statements. Chapters 1 and 19 contain several Simulink models to illustrate various applied math and engineering applications. Appendix B is an introduction to difference equations as they apply to discrete?{time systems, and Appendix C introduces the reader to random generation procedures. This text supplements our Numerical Analysis with MATLAB and Spreadsheet Applications, ISBN 0-9709511-1-6. It is self-contained; the blocks of each library are described in an orderly fashion that is consistent with Simulink! s documentation. This arrangement provides insight into how a model is used and how its parts interact with each another. Like MATLAB, Simulink can be used with both linear and nonlinear systems, which can be modeled in continuous time, sample time, or a hybrid of these. Examples are provided in this text. Most of the examples presented in this book can be implemented with the Student Versions of MATLAB and Simulink. A few may require the full versions of these outstanding packages, and can be skipped. Some add?{ons, known as Toolboxes and Blocksets can be obtained from The MathWorks, Inc., 3 Apple Hill Drive, Natick, MA 01760?{2098, USA, www.mathworks.com.